RITUAL SEBAGAI MEDIA TRANSMISI KREATIVITAS SENI DI LERENG GUNUNG MERBABU - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Tradition developedin a community should continue to bepreservedfrom generations to generations. Efforts are being made one of them may be through the processof transmission or inheritance. Transmission can bedone in various ways, one through the ritual. Rituals performed continuously and regularly can beagood medium in the transmission process.The ritual processof artistic creativity that was developedby the community on the slopes of Mount Merbabu can bean example.Art that goeshand in hand with the ritual can beone of the transmission medium to continue the tradition that already exists. This researchseeksto answer how ritual can bea transmission medium of art precisely at the Slopecreativity in Merbabu. Keyword: rituals, transmission, art creativity